2011
DOI: 10.1111/j.2042-7158.2011.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum polysaccharides antagonize the suppression on lymphocytes induced by culture supernatants of B16F10 melanoma cells

Abstract: B16F10-CS suppressed lymphocyte proliferation and perforin and granzyme B production in lymphocytes after induction with phytohemagglutinin, as well as lymphocyte proliferation in the mixed lymphocyte reaction. This suppression may be associated with elevated levels of immunosuppressive IL-10, TGF-β1 and VEGF in B16F10-CS. Gl-PS had antagonistic effects on the immunosuppression induced by B16F10-CS, suggesting the potential for Gl-PS in cancer immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…in Korea, China and Japan. Many groups suggested the potential role of Ganoderma lucidum in the treatment of various cancers including prostate , skin (Sun et al, 2011), ovarian (Zhao et al, 2011) and colon cancer (Jedinak et al, 2011). Cao et al reported anti-tumor and anti-angiogenic activity of Ganoderma lucidum polysaccharides in vitro and in vivo Lin, 2004, 2006).…”
Section: Inhibitory Effects Of Herbal Medicines On Angiogenesis and Mmentioning
confidence: 98%
“…in Korea, China and Japan. Many groups suggested the potential role of Ganoderma lucidum in the treatment of various cancers including prostate , skin (Sun et al, 2011), ovarian (Zhao et al, 2011) and colon cancer (Jedinak et al, 2011). Cao et al reported anti-tumor and anti-angiogenic activity of Ganoderma lucidum polysaccharides in vitro and in vivo Lin, 2004, 2006).…”
Section: Inhibitory Effects Of Herbal Medicines On Angiogenesis and Mmentioning
confidence: 98%
“…As we previously described [29], Gl -PS is a glycopeptide with a molecular weight of 584,900; the ratio of polysaccharides-to-peptides was 93.61%:6.49%. The polysaccharides consisted of d-rhamnose, d-xylose, d-fructose, d-galactose, d-mannose, and d-glucose with a molar ratio of 0.793:0.964 :2.944:0.167:0.389:7.94, and linked together by β-glycosidic linkages.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, suppression of lymphocytes as well as macrophages caused by B16F10 cell culture supernatants containing immunosuppressive factors, such as TGF-β, IL-10, and VEGF, was antagonized by Gl -PS [29,30,31]. Lymphocyte proliferation, and perforin and granzyme B production in lymphocytes after induction with phytohemagglutinin (PHA), as well as lymphocyte proliferation in the mixed lymphocyte reaction, were suppressed by B16F10 cell culture supernatants in which there were elevated levels of IL-10, TGF-β1, and VEGF, but the suppression was fully or partially antagonized by Gl -PS [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have showed that GLP can mediate cytotoxicity in number of cancer cell lines including lung cancer, prostate cancer and breast cancer. Further studies showed that GLP programmed cell death through endothelial growth factor overexpression and tumor angiogenesis inhibition in highly metastatic mouse melanoma B16F10 cells (Sun et al, 2011), through endotoxin-induced intercellular cell adhesion molecule-1 (ICAM-1) upregulation in the neointima in mice (Liu et al, 2010), through cell differentiation and p53 activation in human monocytic leukemia THP-1 cells (Hsu et al, 2011), through activation of mitochondrial signaling pathway in MCF-7 breast cancer cells (Shang et al, 2011). GLP can also boost anticancer immunity by changing lymphocyte phenotype in H22 hepatoma mice (Zhou et al, 2009), by enhancing CD56 + NK-cell cytotoxicity in cord blood (Chien et al, 2004), by promoting the proliferation of B cells in mice (Jiang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%